The general educator's guide to special education - Maanum, Jody L. 4 0 16; 5 (Thousand Oaks, California : Corwin, 2009)
Provides a guide for educators, including activities and suggestions to help them address the various needs of the special education students in their classrooms.
Includes bibliographical references and index.
Professional.
Keywords: 2 -- 0; 6; Education;Education -- Children with disabilities;Special education;Handicapped children -- United States -- Handbooks, manuals, etc.;Handbooks, manuals, etc.;Handbooks, manuals, etc; 20; 2